ОЦІНКА ЯКОСТІ ПУЛУ АКТИВІВ, СФОРМОВАНОГО ДЛЯ СЕК’ЮРИТИЗАЦІЇ, У КОНТЕКСТІ АНАЛІТИЧНОГО ЗАБЕЗПЕЧЕННЯ СИСТЕМИ МЕНЕДЖМЕНТУ - Byrytska, Olga; Ivanenko, Valentyna (Zhytomyr Ivan Franko State University, 2021)
The lack of an effective methodology for the analysis of asset securitization operations causes problems in the formation of a strategy for managing the process of financing the activities of the initiator of the securitization. The article substantiates the areas of analytical support of the management system in terms of asset securitization: the formation of financial and economic justification of the feasibility and feasibility of securitization of assets (study of potential investors and analysis of prospects for placement of securities; diligence); assessment of the original assets of the originator for the possibility of their securitization; identification of the impact of securitization of assets on the financial performance of the originator; assessment of risks associated with the use of securitization of assets); analysis of the quality of the asset pool generated by the originator for securitization; evaluation of the effectiveness of securitization operations for its initiator. It is also proposed to analyze the quality of the pool of assets generated by the originator for securitization, in the following sequence: assessment of the probability of default and the amount of expected losses on the pool of assets to be securitized; identification of factors influencing the early repayment of pool assets; assessment of the parameters of the formed pool of securitized assets, based on the analysis of its structure and the selected system of indicators; modeling of future payment flows in the pool of securitized assets, which provides the formation of analytical information to decide on the possibility of securitization using the assets available in the originator and diversification of risks through optimal concentration of assets.